Psychometric Characteristics of a Patient Reported Outcome Measure on Ego-Integrity and Despair among Cancer Patients. - Gitta Kleijn; Lenneke Post; Birgit I Witte; Ernst T Bohlmeijer; Gerben J Westerhof; Pim Cuijpers; Irma M Verdonck-de Leeuw (PLoS ONE)
Purpose To evaluate psychometric characteristics of a questionnaire (the Northwestern Ego-integrity Scale (NEIS)) on ego-integrity (the experience of wholeness and meaning in life, even in spite of negative experiences) and despair (the experience of regret about the life one has led, and feelings of sadness, failure and hopelessness) among cancer patients. Methods Cancer patients (n = 164) completed patient reported outcome measures on ego-integrity and despair (NEIS), psychological distress, anxiety and depression (Hospital Anxiety and Depression Scale (HADS)), and quality of life (EORTC QLQ-C30 (cancer survivors, n = 57) or EORTC QLQ-C15-PAL (advanced cancer patients, n = 107)). Confirmatory Factor Analysis was used to assess construct validity. Cronbach's alpha was used to assess internal consistency. Convergent validity was tested based on a priori defined hypotheses: a higher level of ego-integrity was expected to be related to a higher level of quality of life, and lower levels of distress, depression and anxiety; a higher level of despair was expected to be related to a lower level of quality of life, and higher levels of distress, depression and anxiety. Results The majority of all items (94.5%) of the NEIS were completed by patients and single item missing rate was below 2%. The two subscales, labeled as Ego-integrity (5 items) and Despair (4 items) had acceptable internal consistency (Cronbach's alpha .72 and .61, respectively). The Ego-integrity subscale was not significantly associated with quality of life, distress, anxiety, or depression. The Despair subscale correlated significantly (p <.001) with quality of life (r = -.29), distress (r = .44), anxiety (r = .47) and depression (r = .32). Conclusion The NEIS has good psychometric characteristics to assess ego-integrity and despair among cancer patients.